Variability in the meridional overturning circulation at 32°S in the Pacific Ocean diagnosed by inverse box models. (April 2022) - Arumí-Planas, Cristina; Hernández-Guerra, Alonso; Caínzos, Verónica; Vélez-Belchí, Pedro; Farneti, Riccardo; Mazloff, Matthew R.; Mecking, Sabine; Rosso, Isabella; Schulze Chretien, Lena M.; Speer, Kevin G.; Talley, Lynne D.
Highlights: The pattern of circulation changes in 2009 which resembles a "bowed gyre". A Rossby wave forced by wind stress causes an anomalously lower SSHA. Temperature and freshwater transports are altered by the "bowed gyre" circulation. Abstract: The meridional circulation and transport at 32°S in the Pacific Ocean in 1992 and 2017 are compared with analogous data from 2003 and 2009 computed by Hernández-Guerra and Talley (2016). The hydrographic data come from the GO-SHIP database and an inverse box model has been applied with similar constraints as in Hernández-Guerra and Talley (2016). In 1992, 2003 and 2017 the pattern of the overturning streamfunction and circulation are similar, but in 2009 the pattern of the circulation changes in the whole water column. The horizontal distribution of mass transports at all depths in 1992 and 2017 resembles the familiar shape of the "classical gyre" also observed in 2003 and is notably different to the "bowed gyre" found in 2009. The hydrographic data have been compared with data obtained from the numerical modelling outputs of ECCO, SOSE, GLORYS, and MOM. Results show that none of these models properly represents the "bowed gyre" circulation in 2009, and this change in circulation pattern was not observed during the entire length of model simulations. Additionally, the East Australian Current in the western boundary presents higher mass transport in the hydrographic data than in any numerical modelling output. Its poleward mass transport ranges from −35.1 ± 2.0 Sv in 1992 to −54.3 ± 2.6 Sv in 2003. Conversely, the Peru-Chile Current is well represented in models and presents an equatorward mass transport from 2.3 ± 0.8 Sv in 2009 to 4.4 ± 1.0 Sv in 1992. Furthermore, the Peru-Chile Undercurrent presents a more intense poleward mass transport in 2009 (−3.8 ± 1.2 Sv). In addition, the temperature and freshwater transports in 1992 (0.42 ± 0.12 PW and 0.26 ± 0.08 Sv), 2003 (0.38 ± 0.12 PW and 0.25 ± 0.02 Sv), and 2017 (0.42 ± 0.12 PW and 0.34 ± 0.08 Sv) are similar, but significantly different from those in 2009 (0.16 ± 0.12 PW and 0.50 ± 0.03 Sv, respectively). To clarify the causes of these different circulation schemes, a linear Rossby wave model is adopted, which includes the wind-stress curl variability as remote forcing and the response to sea surface height changes along 30°S.